Statement in Support of Revising the Uniform Determination of Death Act and in Opposition to a Proposed Revision. - Shewmon, D Alan (Journal of Medicine & Philosophy, 2023)
Discrepancies between the Uniform Determination of Death Act (UDDA) and the adult and pediatric diagnostic guidelines for brain death (BD) (the "Guidelines") have motivated proposals to revise the UDDA. A revision proposed by Lewis, Bonnie and Pope (the RUDDA), has received particular attention, the three novelties of which would be: (1) to specify the Guidelines as the legally recognized "medical standard," (2) to exclude hypothalamic function from the category of "brain function," and (3) to authorize physicians to conduct an apnea test without consent and even over a proxy's objection. One hundred seven experts in medicine, bioethics, philosophy, and law, spanning a wide variety of perspectives, have come together in agreement that while the UDDA needs revision, the RUDDA is not the way to do it. Specifically, (1) the Guidelines have a non-negligible risk of false-positive error, (2) hypothalamic function is more relevant to the organism as a whole than any brainstem reflex, and (3) the apnea test carries a risk of precipitating BD in a non-BD patient, provides no benefit to the patient, does not reliably accomplish its intended purpose, and is not even absolutely necessary for diagnosing BD according to the internal logic of the Guidelines; it should at the very least require informed consent, as do many procedures that are much more beneficial and less risky. Finally, objections to a neurologic criterion of death are not based only on religious belief or ignorance. People have a right to not have a concept of death that experts vigorously debate imposed upon them against their judgment and conscience; any revision of the UDDA should therefore contain an opt-out clause for those who accept only a circulatory-respiratory criterion.